Influence of irrigation regime and seasonal temperatures on nut quality and the oil fatty acid profile of walnuts (Juglans regia L.) - Calvo, Franco Emmanuel (2023)
Walnut production is expanding worldwide due to the high demand for natural products with proven nutraceutical properties. This expansion includes new growing areas, such as central–western Argentina, where crop water requirements have yet to be determined and little is known about the response in terms of production quality to the water regime. The aim of this study was to assess the effects of four irrigation regimes (at 50, 75, 100, and 125 % of crop evapotranspiration) and the weather conditions over two consecutive seasons in a young Chandler walnut orchard in terms of in–shell and kernel caliber, kernel color, oil concentration, and fatty acid profile. Quality production characteristics were not significantly affected by irrigation regimes within each season. In contrast, the quality parameters achieved were significantly different between seasons. The first season (S1) was wetter (462 mm) and cooler (17.05 °C mean air temperature in the oil accumulation period) and produced more extra–light kernels (92%). The second season (S2) was drier (326 mm) and warmer (19.02 °C) and produced a lower proportion of extra–light kernels (82.2%). In addition, during the second season, walnuts produced larger kernels with a higher oil concentration (62.7%; +3.5% of S1) and a better omega–6/omega–3 ratio (3.25 in S2 vs. 3.70 in S1). These results suggest that kernel quality was more sensitive to the seasonal temperature than the irrigation studied regimes. The nutritional quality of walnuts may increase significantly in warmer seasons/environments despite the deterioration of kernel color.